STUDIES ON THE DISTRIBUTION OF BARNACLE LARVAE AND THE BARNACLE FOULING IN THE ESTUARINE AREA OF MUARA KARANG - Romimohtarto, Kasijan; Arinardi, Okto Haryanto (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Estuary hosts many of the meroplanktonic lives of marine animals, among which are the barnacles. The study of the seasonal abundance of the barnacle larvae and of the barnacle attachments at Muara Karang during 1975-1976 indicated that barnacle larvae and barnacle attachments occurred throughout the year. However, certain peaks of the larvae abundance and the high densities of attachment were found in certain months of the year. The peaks of larvae distribution were observed in April 1975, June 1975, September 1975, and January 1976. In general the density of the attached barnacles on panels was highest during the period of March - August, and lowest during December-February. The physical, biological, and sedimentological factors in relation with the distribution of the barnacle larvae and the density of the attached barnacles were discussed. Two governing factors seemed to be the wave and the sediment load. Relationship between the abundance of the barnacle larvae and the density of attachment was difficult to see.